2022
DOI: 10.35848/1347-4065/aca772
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient spin current source using BiSb topological insulator/NiO bilayers

Abstract: BiSb is a topological insulator with both giant spin Hall effect and high electrical conductivity, which are important for ultralow power spin-orbit-torque magnetoresistive random access memory. However, when a ferromagnetic (FM) thin film is deposited on top of BiSb, large surface roughness and diffusion of Sb out of the BiSb layer into the FM layer results in a much smaller effective spin Hall angle θ SH eff. In this work, we show that by inserting a NiO layer between BiSb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The surface is flatter than previous reports on epitaxial BiSb(0001) with roughness from 0.6 to 1 nm. [19,40,47,59] This low roughness helps to obtain a high-quality interface with the ferromagnetic layer (FM), as required for studying SOTs accurately. Overall, the RHEED, XRD, and AFM measurements demonstrate the successful deposition of twin-free epitaxial Bi 0.9 Sb 0.1 (0001) thin films of the highest quality.…”
Section: Sample Growth and Structural Characterizationmentioning
confidence: 99%
“…The surface is flatter than previous reports on epitaxial BiSb(0001) with roughness from 0.6 to 1 nm. [19,40,47,59] This low roughness helps to obtain a high-quality interface with the ferromagnetic layer (FM), as required for studying SOTs accurately. Overall, the RHEED, XRD, and AFM measurements demonstrate the successful deposition of twin-free epitaxial Bi 0.9 Sb 0.1 (0001) thin films of the highest quality.…”
Section: Sample Growth and Structural Characterizationmentioning
confidence: 99%
“…While spin properties in a TI/insulator/ferromagnetic structure have been observed using electrical methods by some research groups, , efficient spin–orbit torque has been rarely reported. Other researchers have inserted antiferromagnetic oxides, such as NiO, and reported enhanced spin Hall angles of 0.2–10.3 and damping-like torques of B DL / j = 12–300 mT/(10 7 A cm –2 ) in a BiSb/NiO/Co/Pt structure. Thus, the improvement attained by inserting an insulation layer at the interface might not be a general solution.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] This crystallographic orientation is essential for achieving the very large SHE, probably due to the multiple Dirac cones at this surface. Our observation that ion‐beam patterning changes the dominant orientation of an MBE‐grown BiSb film from (003) to (012) may be helpful in optimizing thin‐film preparation for applications in magnetic random access memory devices [ 38–40 ] and skyrmion‐based devices. [ 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Our observation that ion-beam patterning changes the dominant orientation of an MBE-grown BiSb film from (003) to (012) may be helpful in optimizing thin-film preparation for applications in magnetic random access memory devices [38][39][40] and skyrmionbased devices. [41]…”
Section: Hall Measurementsmentioning
confidence: 99%